Black Rats eradicated from Big Green Island in Bass Strait, Tasmania - W Dick; S Robinson (Papers and Proceedings of The Royal Society of Tasmania, 2020)
Big Green Island is a 129-ha Nature Reserve and part of the Furneaux Group of islands in Bass Strait, southeastern Australia. Beginning in April 2016, Black Rats Rattus rattus were targeted for eradication using poisoning with 50 ppm brodifacoum wax blocks via a 25 x 25 m grid of bait stations (16 stations per ha) checked daily for a four-week period followed by three one-week visits over an eight-week period. After six weeks, rodent chew-cards were deployed exposing pockets of rat activity on the island. Island-wide monitoring led to the capture of six rats, the last known rat being killed in November 2016. Monitoring for signs of rats proceeded for a further two years and the island was declared rat-free in November 2018. The project encompassed partnerships between government agencies, industry and non-government organisations, and involved a significant volunteer contribution.